Culture and Function of Electrofusion-Derived Clonal Insulin-Secreting Cells Immobilized on Solid and Macroporous Microcarrier Beads. Issue 3 (June 2000) - Hamid, M.; McCluskey, J. T.; McClenaghan, N. H.; Flatt, P. R.
Abstract : In view of the advantages of the bulk production of clonal pancreaticbeta cells, an investigation was made of the growth and insulin secretoryfunctions of an electrofusion-derived cell line (BRIN-BD11) immobilizedon a solid microcarrier, cytodex-1 or a macroporous microcarrier, cultispher-G. For comparison, similar tests were performed usingBRIN-BD11 cells present in single cell suspensions or allowed toform pseudoislets. Similar growth profiles were recorded for eachmicrocarrier with densities of 4.4×10 5 ±0.3 cells/ml and4.2×10 5 ±0.2 cells/ml achieved using cytodex-1 andcultispher-G, respectively. Cell viability began to decline on day 5 ofculture. Insulin concentration in the culture medium reached a peak of26±2.0 ng/ml and 24±2.2 ng/ml for cells grown oncytodex-1 and cultispher-G, respectively. Cells grown on both types ofmicrocarrier showed a significant 1.5–1.8-fold acuteinsulin-secretory response to 16.7 mmol/l glucose. L-alanine (10 mmol/l) andL-arginine (10 mmol/l) also induced significant 3–4 fold increasesof insulin release. BRIN-BD11 cells immobilized on cytodex-1 or cultispher-Gout-performed single cell suspensions and pseudoislets in terms ofinsulin-secretory responses to glucose and amino acids. A 1.3-fold, 2.2-fold and 1.7-fold stimulation of insulin secretion was observed forglucose, L-alanine and L-arginine respectively in single cellsuspensions. Corresponding increases for pseudoislets were1.6–1.8-fold for L-alanine and L-arginine, with no significantresponse to glucose alone. These data indicate the utility ofmicro-carriers for the production of functioning clonal beta cells.